Deceased Donor Organs: What Can Be Done to Raise Donation Rates Using Evidence From Malaysia?. Issue 5 (14th January 2016) - Rasiah, R.; Manikam, R.; Chandrasekaran, S. K.; Naghavi, N.; Mubarik, S.; Mustafa, R.; Pushparajan, S.
Abstract : Organ donation rates have continued to fall seriously short of needs worldwide, with the lowest rates recorded among developing economies. This study seeks to analyze evidence from a developing economy to explore the usefulness of social psychological theory to solve the problem. The study deployed a large survey (n = 10 412) using a convenience sampling procedure targeted at increasing the number of Malaysians registered with the Ministry of Health, Malaysia who are willing to donate organs upon death. Structural equation modeling was deployed to estimate simultaneously the relative influence of cognitive and noncognitive variables on willingness to donate deceased organs. The cognitive factors of donation perception, socioeconomic status and financial incentives, and the noncognitive factors of demography and fear showed a high statistically significant (1%) relationship with willingness to donate organs after death. While financial incentives were significant, cash rewards showed the least impact. Donation perception showed the highest impact, which shows that the development of effective pedagogic programs with simultaneous improvements to the quality of services provided by medical personnel engaged in retrieving and transplanting deceased donor organs can help raise organ donation rates. Abstract : Using structural equation modelling from a large Malaysian survey, this study shows that it is possible to raise deceased organ donation rates through awareness campaigns that focus on developing the cognitive variables.